Improving Nursing Care Quality During the COVID-19 Pandemic: The Role of Transformative Technologies - Kiarostami, Nahid (Digital Repository of Theses, 2025)
Concerns about the quality of nursing care have grown in the wake of the enormous difficulties brought on by the COVID-19 pandemic. In light of the continuing epidemic, this article explores the critical function of revolutionary technology in improving the standard of nursing care. Insights into nurses' use of electronic instruments and platforms to address COVID-19's specific difficulties are provided. A foundational component of these technologies, telemedicine has allowed doctors to remotely confer with patients and keep tabs on them, lowering risk and increasing accessibility to treatment. Further benefits include better care coordination, fewer mistakes, and easier exchange of data among healthcare providers made possible by electronic health records. Nurses may now keep tabs on their patients' vitals from afar with the use of telemonitoring technology, which opens the door to early intervention and individualized treatment programs. Additionally, the patient-nurse collaboration has been strengthened by the promotion of self-management and patient engagement through the use of wearable devices and mobile applications. Finally, during the COVID-19 epidemic, revolutionary technology have completely transformed the quality of nursing care. As a result, nurses now play a more integral part in healthcare delivery, and their capacity to respond to changing circumstances is better. In order to maintain patient-oriented, efficient, and safe nursing care as the pandemic continues, it is crucial to utilize these tools. Keywords: Technologies Nursing Care, Transformative, COVID-19 Pandemic